2018
DOI: 10.1039/c8nj01656a
|View full text |Cite
|
Sign up to set email alerts
|

Visible-enhanced photocatalytic performance of CuWO4/WO3 hetero-structures: incorporation of plasmonic Ag nanostructures

Abstract: A new plasmonic Ag hybridized CuWO4/WO3 heterostructured nanocomposite was successfully synthesized via a ligand-assisted sol gel method and the photocatalytic activity was evaluated by photo-degradation of methylene blue (MB) under visible light irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…The optical properties of the fillers used in light-curable dental composites is considered as a primary factor affecting curing depth, which is proportional to the physical properties and longevity of restorations. To investigate the optical characteristics of Sr-HA under illumination, we computed the energy-loss spectra by converting the computed complex dielectric functions [49,50,51].…”
Section: Resultsmentioning
confidence: 99%
“…The optical properties of the fillers used in light-curable dental composites is considered as a primary factor affecting curing depth, which is proportional to the physical properties and longevity of restorations. To investigate the optical characteristics of Sr-HA under illumination, we computed the energy-loss spectra by converting the computed complex dielectric functions [49,50,51].…”
Section: Resultsmentioning
confidence: 99%
“…Photon absorption and charge generation/separation might generally be affected by surface plasmon resonance (SPR) phenomena [38]. Similarly, we recently reported on the significant increase in photocatalytic activity of CuWO 4 /WO 3 composites by modification with Ag nanostructures for water treatment applications [39].…”
Section: Introductionmentioning
confidence: 92%
“…Copper nitrate hydrate, polyvinylpyrrolidone (PVP, M w = 29000), ammonium metatungstate hydrate (AMT), AgNO 3 and ethylene glycol (EG), all with high purity grade (99%, Sigma-Aldrich) were used. CuWO 4 /WO 3 was prepared similar to our previous report [39].…”
Section: Materials Synthesis and Film Preparationmentioning
confidence: 99%
“…20 The band gap structure of WO 3 limits the practical application. 21 In order to solve these problems, many methods, [22][23][24][25][26][27] including morphology regulation, dye sensitization, metal and nonmetal doping, composite supporting, and coupled semiconductors, [28][29][30][31][32] have been used. For example, Duanmu et al 33 reported a heterojunction composed of a WO 3 square microplate and CuWO 4 nanoparticles fabricated through a twostep hydrothermal method, and the WO 3 -CuWO 4 hetero-material showed an excellent sensing property toward n-butanol.…”
Section: Introductionmentioning
confidence: 99%